Moxibustion treatment and nursing of a patient with peripheral neuropathic pain of lower limbs caused by oxaliplatin (艾灸疗法治疗1例奥沙利铂致下肢周围神经病变性疼痛的护理) - ZHANG Yue (张悦); LIU Shuhong (刘书红) (Association of Integrative Nursing, 2023)
To summerize the effect of moxibustion therapy and nursing interventions on the peripheral neuropathic pain of lower limbs caused by oxaliplatin. A comprehensive pain assessment was conducted for the establishment of following nursing plan. The combination treatment of moxibustion and acupoint massage was carried out to relive the peripheral neuropathic pain of lower limbs and ensure the completion of chemotherapy. (本文总结1例艾灸疗法缓解奥沙利铂致下肢周围神经病变性疼痛的护理经验。评估患者疼痛程度, 明确干预方案, 先用生姜涂擦, 再用艾灸条艾灸下肢, 并进行穴位按摩。通过肿瘤绿色调护, 有效减轻患者下肢周围神经病变性疼痛, 保障化疗的顺利进行, 对提高患者生存质量具有积极意义。)